Very short fairly interesting and reasonably cheap book about studying organizations - "Grey, Chris" (New Delhi, 2005)
Should You Buy this Book?-- Introduction -- Why Studying Organizations Matters to Me -- Part one: studying organizations - classical approaches -- Bureaucracy and Scientific Management -- Human Relations Theory and People Management -- Part two: studying organizations - contemporary approaches -- Organizational Culture and Self-Management -- Post-Bureaucracy and Change Management -- Part three: organizing studies -- Business Schools and Professional Management -- Conclusion -- Why Should Studying Organizations Matter to You?
includes bibliographical references and index
Keywords: Organization behaviour